Politics, Poverty and the Church in an ‘Age of Austerity’ - Chris Shannahan; Stephanie Denning (Religions, 2022)
The ‘Age of Austerity’ has ruptured the social fabric of contemporary Britain. Arising from our three-year Life on the Breadline project, this article represents the first fieldwork-led analysis of the multidimensional nature of austerity-age poverty by academic theologians in the UK. The article analyses the impact that austerity has had on Christian responses to poverty and inequality in the UK. We draw on our six ethnographic case studies and interview responses from over 120 national and regional Church leaders to exemplify the four approaches to the Christian engagement with poverty that we identified during our research: ‘caring’, ‘campaigning and advocacy’, ‘enterprise’ and ‘community building’. We argue that the Church needs to grasp the systemic, multidimensional and violent nature of poverty in order to realise the potential embedded in its extensive social capital and fulfil its goal of ‘transforming structural injustice’. The paper shows that the Church remains nervous of moving beyond welfare-based responses to poverty and suggests that none of the existing approaches can force poverty into retreat until the Church re-imagines itself as a liberative movement that embodies God’s preferential option for the poor in every aspect of its life and practice.